Predicting Mortality and ICU Admission in Trauma: An Emergency Nursing Comparison of NEWS, RTS, and MREMS - Yunanto, Rismawan; Maysaroh, Salma; Setioputro, Baskoro; Haristiani, Ruris; 'Ala, Muhamad Zulfatul (Universitas Muhammadiyah Surakarta, 2026)
Trauma is a global health problem, which is a serious issue, claiming around 8% of all lives lost. Proper treatment is crucial, and accurate assessment is key. Coming hotfooting out of nowhere or being involved in a sudden accident are two of the most common causes. Many methods have been established for the determination of trauma and for the guidance of treatment. This study attempted to compare the performance of NEWS, MREMS, and RTS in predicting death and ICU admission among trauma patients in Indonesia. This cross-sectional design analyzed 90 trauma patients admitted to the hospital in 2024. Patients aged ≥ 16 years with complete medical records were included. The instruments used to predict mortality and ICU admission were NEWS (National Early Warning Score), RTS (Revised Trauma Score), and MREMS. The analysis was conducted by comparing the predictive performance using AUCROC with the optimal threshold value by the Youden index. The Odds Ratio (OR) value was also determined. The analysis of this study was conducted using SPSS version 29. Interpretation results with p < 0.05 were considered significant. The results of this study analysis showed that the three scoring systems (NEWS, RTS, and MREMS) had excellent discriminatory ability to predict mortality (AUCROC ≥ 0.95, p < 0.001), with NEWS achieving the highest performance (AUCROC 0.979, sensitivity 0.966, specificity 0.883) compared to other instruments. In the ICU admission variable, the predictive performance results were lower, but NEWS still had a better value (AUCROC 0.816) compared to the others. This analysis concludes that the three instruments have acceptable discriminative power. NEWS is a superior instrument, as evidenced by better descriptive results for sensitivity and specificity in predicting trauma mortality and ICU admission. This finding further validates the usability of NEWS as an effective triage tool for predicting early risk of mortality and ICU admission in trauma patients.